Coexistence in the Public Spaces of Latin American Cities (Convivencia en Los Espacios Públicos de Las Ciudades Latinoamericanas) - Muñoz-Lagos, A (TAYLOR & FRANCIS LTD, 2021)
This article presents the findings of a descriptive correlational study that investigates personal evaluations of behaviours that characterize coexistence in public spaces in cities in seven Latin American countries. A total of 1,337 people of different genders and age groups participated in the research, evaluating the contribution of different behaviours associated with coexistence through an ad hoc questionnaire containing 50 items. Multidimensional scaling analysis (SSA) indicates that people assess the behaviours explored based on the function they attribute to coexistence. Albeit with some variations, there are overlaps in several of the dimensions into which the items in the questionnaire were grouped, including, for most cities, safety, environmental protection, socialization and mobility. The results are discussed on the basis of cultural differences, the consequences for quality of urban life and the formulation of public policy for citizen education. © 2021 Fundacion Infancia y Aprendizaje.